Analysis of Superconductor of Nd1Ba2Cu3O7 and Nd3Ba5Cu8O18 Phases Using FTIR Spectrophotometer - Putra Adnyana, IGA; Sumadiyasa, Made; Wendri, Nyoman (BULETIN FISIKA; Vol 21 No 2 (2020): BULETIN FISIKA, 2020)
I has been synthesized superconducting materials of the Nd 1 Ba 2 Cu 3 O 7 , Nd 3 Ba 5 Cu 8 O 18 and Y 3 Ba 5 Cu 8 O 18 phases. The study was conducted to determine whether the data from the phase Y 1 Ba 2 Cu 3 O 7 can be used as a base to identify superconducting material of the Nd 3 Ba 5 Cu 8 O 18 phase. Synthesis was done by solid state reaction method with initial mixing in HNO 3 solution mixture with Y 2 O 3 , Nd 2 O 3 , BaCO 3 , and CuO, with the ratio adjusted to the stoichiometry calculation. Samples in the form of pellets with a diameter of 1.5 cm were sintered at 950 o C for 24 hours in an atmospheric environment. The FTIR measurements have been carried out with a standard KBr. The theoretical calculation spectra and vibration mode data from YBa 2 Cu 3 O 7- d  can be used to identify Nd 1 Ba 2 Cu 3 O 7 , Nd 3 Ba 5 Cu 8 O 18 dan Y 3 Ba 5 Cu 8 O 18 , with peak absorption in the range of wave numbers that are almost the same, namely 400-450 cm -1 , which is the four oxygen atoms O(2,3) mode, 426-439 cm -1 is the in-phase mode of oxygen atom O(2,3), and the vibrational mode of peaks O(4) is observed at 488 cm -1 .